Community based social marketing for implementation of energy saving targets at local level - Dalia Streimikiene; Jolita Vveinhardt (Amfiteatru Economic Journal, 2015)
Energy saving and greenhouse gas (GHG) emission reduction policies at local level need to be investigated and new tools for climate change mitigation are necessary seeking to achieve GHG emission targets in Lithuania. Most Lithuanian municipalities have signed Covenant of Mayors and have prepared local energy action plans. However, all these plans include just energy saving measures on supply side and renovation of buildings. Nevertheless, the significant energy savings and GHG emission reductions can be achieved through behavioural changes. The aim of the paper is to apply community based social marketing approach in assessment of achievable energy saving and GHG emission reduction targets set by local energy action plans. The paper presents the results of case study implemented in Kaunas region municipality. The case study was conducted by creating focus groups and applying two scenarios: baseline or doing nothing and climate change mitigation scenario including intervention measures. The results of case study revealed that the total energy consumption reduction target set in Sustainable energy development strategy of Kaunas region county - 11% - can be achieved by combining results of energy consumption reduction in both focus groups. The survey conducted after study finalization revealed that respondents were provided with a lot of additional knowledge during the study and achieved real money savings. The major barriers of energy savings in households are related with the lack of information on energy savings and GHG emission reduction.
Keywords: Q41; Q5; Q58; R21; R58; 330; community based social marketing; local energy plans; energy savings; GHG emission reductions